2007
DOI: 10.1109/vetecs.2007.249
|View full text |Cite
|
Sign up to set email alerts
|

Performance of MIMO with Frequency Domain Packet Scheduling in UTRAN LTE Downlink

Abstract: This paper addresses the performance of spatial division multiplexing (SDM) multiple-input multiple-output (MIMO) techniques together with frequency domain packet scheduling (FDPS) based on UTRAN Long Term Evolution (LTE) downlink. Two SDM concepts currently considered in 3GPP are the single-user (SU-) and the multi-user (MU-) MIMO. For MU-MIMO, multiple users can be scheduled on different streams on the same time-frequency resource, while SU-MIMO restricts one time-frequency resource to a single user. Both co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 10 publications
0
28
0
4
Order By: Relevance
“…A study of the PF scheduler performance applied to a video streaming in HSDPA-based cellular system can be found in [19]. The PF scheduler is commonly used as a reference scheduler for the experiments performed among others in [13] and [21].…”
Section: Previous Workmentioning
confidence: 99%
“…A study of the PF scheduler performance applied to a video streaming in HSDPA-based cellular system can be found in [19]. The PF scheduler is commonly used as a reference scheduler for the experiments performed among others in [13] and [21].…”
Section: Previous Workmentioning
confidence: 99%
“…Denote by ζ k the set of users scheduled on the k th PRB and |ζ k | = n t . Without precoding, the received signal vector at the jth MS, j ∈ ζ n , can be modeled as y n,j = H n,j x n + n n,j , where n n,j ∈ C nr×1 is a circularly symmetric complex Gaussian noise 2 In the localized FDMA transmission scheme, each user's data is transmitted by consecutive subcarriers, while for the distributed FDMA transmission scheme, the user's data is transmitted by distributed subcarriers [1]. 1 vector with a zero mean and covariance matrix N 0 I ∈ R nr×nr , i.e., n n,j ∼ CN (0, N 0 I); H n,j ∈ C nr×nt is the channel matrix between the BS and the jth MS at the nth PRB and x n ∈ C nt×1 is the transmitted signal vector at the nth PRB, and the µth element of x n is the data symbol x n,µ transmitted from the µth MS, µ ∈ ζ n .…”
Section: System Modelmentioning
confidence: 99%
“…With the localized transmission 1 Open loop and closed loop MIMO correspond to the MIMO systems without and with channel state information at the transmitter, respectively [1]. 2 In the localized FDMA transmission scheme, each user's data is transmitted by consecutive subcarriers, while for the distributed FDMA transmission scheme, the user's data is transmitted by distributed subcarriers [1].…”
Section: System Modelmentioning
confidence: 99%
“…SDM is used to improve the spectral efficiency of the system, while FDPS allows the packet scheduler at the Base Station (BS) to exploit the available multiuser diversity in both time and frequency domain. In [2], it is shown that the MIMO schemes with combined SDM and FDPS can further enhance the system performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation